Specific morphology of coronary artery aneurysms in mainly white patients with Kawasaki disease: initial data from the cardiac catheterization in Kawasaki disease registry - Weisser, Julia; Arnold, Leonie; Wällisch, Wolfgang; Quandt, Daniel; Opgen-Rhein, Bernd; Riede, Frank-Thomas; Gräfe, Florentine; Michel, Jörg; Arnold, Raoul; Schneider, Heike; Tanase, Daniel; Herberg, Ulrike; et al. (Journal of the American Heart Association, 2024)
BACKGROUND: Patients with Kawasaki disease (KD) with coronary artery involvement require long-term cardiac care. Although respective evidence-based recommendations are missing, cardiac catheterization is still considered the gold standard for diagnosing detailed coronary pathology. Therefore, to better understand coronary artery pathology development, we conducted a survey to document and evaluate cardiac catheterization data in a European population. - METHODS AND RESULTS: We retrospectively analyzed cardiac catheterization data from KD children from the year 2010 until April 2023. This registry covers basic acute-phase clinical data, and more importantly, detailed information on morphology, distribution, and the development of coronary artery pathologies. A total of 164 mainly White patients (65% boys) were included. A relevant number of patients had no coronary artery aneurysm (CAA) at the cardiac catheterization, indicating that distal CAAs were almost exclusively detected alongside proximal CAAs. Patients with multiple CAAs revealed a significant positive correlation between the number of CAAs and their dimensions in diameter and in length. Location of the CAA within the coronary artery, age at onset of KD, or natal sex did not significantly influence CAA diameters, but CAAs were longer in older children and in boys. - CONCLUSIONS: That distal CAAs were only present together with proximal ones will hopefully reduce diagnostic CCs in patients with KD without echocardiographically detected proximal CAAs. Furthermore, this study gives valuable insights into dimensional specifics of CAAs in patients with KD. As an ongoing registry, future analyses will further explore long-term outcomes and performed treatments, helping to refine clinical long-term strategies for patients with KD. - REGISTRATION: URL: https://drks.de/; Unique Identifier: DRKS00031022.